Análise da influência do cooperativismo de crédito nos setores da economia na Região Oeste do Paraná - Reis, Sandro Ricardo (2024)
The main objective of the research is to analyze credit cooperativism and its influence on the development of agribusiness; As a specific objective, to show how credit cooperatives were active in the economy of the western region of Paraná; show its essence and its development over the years, and its evolution to the present day; The basis for creating this research was to objectively show what credit cooperatives as a whole are; its ideals, its principles and its organization. Credit cooperatives have been present in the daily lives of people from Paraná for many years, however, part of the population does not have a clear vision and knowledge about it.